Answer:
Solved (x-3/4)(x+1/4)
Explanation:
16x²-8x-3=0
we can find the factors of the above quadratic equation using shridharacharya formula which given as
![x=(-b\pm √(b^2-4ac) )/(2a)](https://img.qammunity.org/2020/formulas/mathematics/high-school/e7vfp9bwgt0u5jzem3ndaljl3t2agny4bk.png)
a= 16, b= -8 and c= -3 putting these values in above equation we can find the factors of x as
![x=(8\pm √(8^2-4*16*(-3)) )/(2*16)](https://img.qammunity.org/2020/formulas/mathematics/high-school/2x4p79x51t5zetoo9op85i8p1zozeta80m.png)
x= 3/4 and -1/4
now 16x²-8x-3 can also be written as (x-3/4)(x+1/4) as 3/4 and 1/4 are the roots of the equation.
on solving expression is equivalent to the original: 16x²-8x-3 we will again obtain 16x²-8x-3. Hence it is varified that the factored expression is equivalent to the original: 16x²-8x-3